First Record of Alphitophagus bifasciatus (Say) (Coleoptera: Tenebrionidae) from Greece; Its Occurrence in Cereal Product Stores - Buchelos ΤΗ.; Athanassiou, C. G. (ENTOMOLOGIA HELLENICA, 1993)
[no abstract available]